'We will multiply the fires of resistance': The catalysts of dissent against institutional science and their interplay with refused knowledge communities. (January 2023) - Bory, Paolo; Giardullo, Paolo; Tosoni, Simone; Turrini, Valentina
Drawing on a 12-month virtual ethnography on the main online spaces of three refused knowledge communities (RKCs) in Italy, this study aims at contributing to the debate on emerging forms of science-related populism from a two-fold perspective. First, we identify and describe the main features and the role played by an understudied figure who we label the 'catalyst of dissent' – a public influencer who does not belong to the scientific community and contributes to the spread of science-related populist narratives within a grassroots ecosystem of resistance to institutional science. Second, our research highlights how RKCs – communities proposing visions of science and medicine denied acceptance or even consideration by institutional science – can appropriate some key resources produced by the catalysts. The analysis focuses on the interplay between the catalysts and three main RKCs during the pandemic crisis in Italy: The No-5G, the Free-Vax, and the 5 Biological Laws communities.